2008
DOI: 10.17014/ijog.vol3no4.20084
|View full text |Cite
|
Sign up to set email alerts
|

Deep Sea Sediment Gravity Flow Deposits in Gulf of Tomini, Sulawesi

Abstract: Micro plate collision against the Eastern Arm of Sulawesi since Pliocene has resulted in a major supply of terigenous sediments into Late Miocene rift-basins in Gulf of Tomini. Studies on offshore multi-channel seismic reflection data complemented by published on-land geological data indicate a series of tectonic events that influenced the depositional system in the Gulf of Tomini. During the Late Neogene, alternating pulses of terigenous sediments were deposited in the basins in the form of deep-sea slump-tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
(12 reference statements)
1
6
0
Order By: Relevance
“…The depositional setting and seismic facies are typical for active slope mass-flow progradation of basin fill complex (Vail et al, 1977). The same reflector is also recognized in the entire Tomini basin (Kusnida and Subarsyah, 2008). This reflection character and configuration suggests an alternation of slump deposits at the slope of the basin and debrite or turbidite and thin bedded pelagic sediments toward the center of the basin.…”
Section: Seismic Sequence 2 (Syn-extension Sequence)supporting
confidence: 63%
“…The depositional setting and seismic facies are typical for active slope mass-flow progradation of basin fill complex (Vail et al, 1977). The same reflector is also recognized in the entire Tomini basin (Kusnida and Subarsyah, 2008). This reflection character and configuration suggests an alternation of slump deposits at the slope of the basin and debrite or turbidite and thin bedded pelagic sediments toward the center of the basin.…”
Section: Seismic Sequence 2 (Syn-extension Sequence)supporting
confidence: 63%
“…Furthermore, the interpretation is validated or confirmed by the existing seismic sections. The seismic sections referred to as "LineDeep" (Rudyawan et al, 2014) and "Line_30" (Kusnida, 2008;Kusnida & et al, 2012;Subarsyah & Sahudin, 2016) are shown in Figure 10 respectively. The positions and orientations of the line locations are displayed on the map in Figure 8.…”
Section: Discussionmentioning
confidence: 99%
“…The tectonic system of Sulawesi Island is characterized by the westward motion of the PSP, the southeastward movement of the ECP with the western region acting as a relatively steady reference point, the southward movement of the CSP, and the north-westward movement of the ABP. These plate interactions form a fascinating and enigmatic tectonic framework within Sulawesi Island (Walpersdorf et al, 1998a;1998b;Kopp et al, 1999;Kusnida, 2008;Martosuwito, 2012). The existence of isolated volcanic island in the study area, i.e.…”
Section: Geological Settingsmentioning
confidence: 99%
“…KusniDa, subarsyah, and b. nirwana in the Tomini Basin consists of shallow marine deposits such as sandstones and reefs forming a potential petroleum system. In contrast, Kusnida and Subarsyah (2008) indicate alternating pulses of terrigenous sediments in the form of deep-sea slump-turbidite-pelagic sediments that changed gradually into a deep-sea pelagic fill system toward the centre of the basins. These two different opinions may lead to the assumption that the Tomini Basin can possibly be underlain by continental or oceanic-like crust.…”
Section: Basement Configuration Of the Tomini Basin Deduced From Mari...mentioning
confidence: 94%